Спроби налагодження польсько-українського діалогу міжвоєнного періоду: сподівання та реалії - Вялова, Ю. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2020)
У статті представлено та переосмислено спроби налагодження польсько-українського діалогу міжвоєнного двадцятиріччя у Другій Речі Посполитій. Зроблено висновок, що за роки панування на західноукраїнських землях польська влада так і не спромоглася виробити якусь цілісну програму розв’язання «українського питання», натомість намагаючись насильницькими методами зламати опір українців. Загалом уся національна політика Польської держави міжвоєнного періоду характеризувалася невизначеністю, половинчастими рішеннями та несправедливими й жорстокими дискримінаційними заходами стосовно українців. З українського боку конструктивний діалог ускладнювала також пропаганда радикальних сил, які проголошували, що немає потреби шукати компромісу з поляками, а будь-які спроби порозуміння характеризували як «національну зраду». Національний екстремізм з обох сторін зумовлював подальше загострення стосунків, що вибухнуло, зокрема, Волинською трагедією 1943 р. У підсумку це призвело до радикалізації українського національного руху, послаблення Польської держави і згодом коштувало обом народам численних жертв унаслідок силового придушення національного розвитку українців і поляків, що тривало десятки років. Водночас, існує багато прикладів польсько-української співпраці інтелектуальних еліт міжвоєнного періоду, які не лише спостерігали та констатували, але і здійснювали практичні кроки в цьому напрямі. The article presents and rethinks the attempts to establish a Polish- Ukrainian dialogue in The Second Polish Republic between the First and Second World Wars. The strategic partnership between Poland and Ukraine has been maintained for the last thirty years. The state of this bilateral relations remains one of the determining factors of regional stability, especially in the context of deterring external threats. The long and contradictory history of Polish- Ukrainian relations is not only the subject of emotional scientific discussions, but also plays the role of a factor that contributes to the growth of ideological and political confrontation, while influencing the current policy of both countries. Interethnic relations in The Second Polish Republic continue to be interpreted differently by Polish and Ukrainian historians. In view of this, the search for and rethinking the facts of attempts to establish a Polish-Ukrainian dialogue between the First and Second World Wars is becoming especially relevant today. It is concluded that during the years of domination in Western Ukraine, the Polish authorities have failed to develop a comprehensive program to resolve the “Ukrainian question”, instead trying to break the resistance of Ukrainian by force. In general, the entire national policy of the Polish state of the interwar period was characterized by uncertainty, half-hearted decisions and unjust and cruel discriminatory measures against Ukrainians. On the Ukrainian side, the constructive dialogue was also complicated by the propaganda of radical forces, which proclaimed that there was no need to seek a compromise with the Poles, and characterized any attempts at understanding as national treason. National extremism on both sides led to further aggravation of relations, which erupted, in particular, the Volyn tragedy of 1943. As a result, it led to the radicalization of the Ukrainian national movement, the weakening of the Polish state, and subsequently cost both nations numerous casualties as a result of the violent suppression of the national development of Ukrainians and Poles that lasted for decades. At the same time, there are many examples of Polish-Ukrainian cooperation of intellectual elites of the interwar period, which not only observed and stated, but also took practical steps in this direction.